W sprawie poprawnej klasyfikacji nazwy wodnej kurzyna - Sosnowski, Jan; Witczak, Krzysztof Tomasz (Slavia Occidentalis, 2015)
According to Jerzy Duma (1999a: 135; 1999b: 93) and Urszula Bijak (2013: 156), the river name Kurzyna (attested in 1564–1565), referring to the upper course of the river Wolbórka, derives from the appellative kura (f.) ‘hen’ or perhaps from the personal name *Kura by the means of the suffix *-ina. This explanation seems impossible for formal reasons. The river name in question is evidently motivated by the forest name Kurzyna (located near the town Tuszyn), mentioned by Jan Łaski (silva dicta Kurzyna) as early as in 1511–1522. Łaski informed also that a small stream flows out from the forest Kurzyna (in torrente ex Cyrzyna decurrente). It is suggested that the name of the forest Kurzyna derives from the Old Polish noun kurzyna (f.) ‘beard lichen, Usnea barbata (L.) Weber’. The river name Kurzyna repeats undoubtedly the homonymic forest name.